2005
DOI: 10.1242/jcs.02584
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin endocytosis regulates the activity of Rap1: a traffic light GTPase at the crossroads between cadherin and integrin function

Abstract: The coordinate modulation of cadherin and integrin functions plays an essential role in fundamental physiological and pathological processes, including morphogenesis and cancer. However, the molecular mechanisms underlying the functional crosstalk between cadherins and integrins are still elusive. Here, we demonstrate that the small GTPase Rap1, a crucial regulator of the inside-out activation of integrins, is a target for E-cadherin-mediated outside-in signaling. In particular, we show that a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
165
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(174 citation statements)
references
References 79 publications
8
165
0
1
Order By: Relevance
“…This involves Src and is triggered by internalization of E-cadherin. Since Rap1 also regulates integrins, these observations indicate the complex role of Rap1 signalling in cell adhesion (Balzac et al, 2005).…”
Section: Activation Of Rap1 By Cell-cell Contactsmentioning
confidence: 83%
“…This involves Src and is triggered by internalization of E-cadherin. Since Rap1 also regulates integrins, these observations indicate the complex role of Rap1 signalling in cell adhesion (Balzac et al, 2005).…”
Section: Activation Of Rap1 By Cell-cell Contactsmentioning
confidence: 83%
“…Secondly, we used the potent ATPase inhibitor, bafilomycin A1. 20 Biotinylation assays revealed that bafilomycin A1 increased the E-cadherin intracellular pool, likely as a consequence of this drug's effects on derailing the recycling from intracellular pools back to the membrane (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work on other members of the cadherin family, in most cases E-cadherin, has shown that these adhesion molecules can control integrin activity 48,49 . At the molecular level, this has been linked to the small GTPase Rap1, a mediator of integrin inside-out activation 10,50 .…”
Section: Discussionmentioning
confidence: 99%